Bioanalytical method development and validation for quantification of amivantamab in rat plasma by LC-MS/MS - Pridhvi Krishna Gaddey; Raja Sundararajan (Future Journal of Pharmaceutical Sciences, 2024)
Abstract Background Amivantamab is a monoclonal bispecific anti-EGFR-MET antibody used to treat non-small cell lung cancer. There were no published methods using a liquid chromatographic—tandem mass spectrometric approach to develop and validate a feasible, novel, and thoroughly validated method for quantifying amivantamab in rat plasma. Results The liquid–liquid extraction method was used to extract the analyte from rat plasma. The analyte was separated using acetonitrile–ammonium formate buffer (40:60) as a mobile phase on waters, alliance e-2695 model high-pressure liquid chromatographic system having Agilent eclipse C18, 150 mm × 4.6 mm, 3.5 µm column. The overall runtime was 6 min at a 1.0 ml/min flow rate. The method showed significant sensitivity and acceptable linearity over the 5.00–100.00 ng/ml concentration range. Accuracy was proved by mean percent recovery ranging from 98.03 to 99.99%. The intraday precision coefficient of variation (%) ranged between 0.31 and 5.43. Also, the findings such as C max, t max, AUC0− t , AUC0− ∞, and half-life values of amivantamab showed that the technique was helpful for pharmacokinetic studies. Conclusions All the validated parameters were found to be within the acceptable range. The validated method was found to be simple, accurate, precise, and reproducible and hence can be used for the routine analysis of amivantamab, such as in-process quality control by liquid chromatographic—tandem mass spectrometry.